Vegetation Response to Holocene Climate Change in the Qinling Mountains in the Temperate–Subtropical Transition Zone of Central–East China - Zhang, Yao; Cui, Qiaoyu; Huang, Youliang; Wu, Duo; Zhou, Aifeng (Frontiers in Ecology and Evolution, 2021)
Global warming is having a profound influence on vegetation and biodiversity patterns, especially in alpine areas and high latitudes. The Qinling Mountain range is located in the transition zone between the temperate and subtropical ecosystems of central–east China and thus the vegetation of the area is diverse. Understanding the long-term interactions between plant diversity and climate change can potentially provide a reference for future landscape management and biodiversity conservation strategies in the Qinling Mountains region. Here, we use a pollen record from the Holocene sediments of Daye Lake, on Mount Taibai in the Qingling Mountains, to study regional vegetation changes based on biomes reconstruction and diversity analysis. Temperature and precipitation records from sites close to Daye Lake are used to provide environmental background to help determine the vegetation response to climate change. The results indicate that climate change was the main factor influencing vegetation and palynological diversity in the Qinling Mountains during the Holocene. The cold and dry climate at the beginning of the early Holocene (11,700–10,700 cal yr BP) resulted in a low abundance and uneven distribution of regional vegetation types, with the dominance of coniferous forest. During the early Holocene (10,700–7000 cal yr BP), temperate deciduous broadleaf forest expanded, palynological diversity and evenness increased, indicating that the warm and humid climate promoted vegetation expanding. In the middle Holocene (7000–3000 cal yr BP), the climate became slightly drier but a relatively warm environment supported the continued increase in palynological diversity. After ~3000 cal yr BP, palynological diversity and the evenness index commenced a decreasing trend, in agreement with the decreased temperature and precipitation in the Qinling Mountains. It’s noteworthy that human activity at this time had a potential influence on the vegetation. During the past few centuries, however, palynological diversity has increased along with the global temperature, and therefore it is possible that in the short-term ongoing climatic warming will promote the vegetation development and palynological diversity in the area without human interference.